At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
Are you sure it isn't 420? If it is, it is 6 and 70
no unfortunely it is 430.
x*y = 430 x+y = 76
x*y = 430 y = 76-x
x*(76-x)=430 y = 76-x
what do u mean factors? do u mean just 2 numbers?
76x-x^2 = 430 y = 76-x
like a . b = 430 and then a+b=76
OMG this place crashes too much so: -x^2 +76x - 430 = 0
let's see if discriminant works: D = 76^2 - 4 * (-1) * (-430) = 5776 - 1720 = 4056
Uhmm.. r us sure the problem is right? Because radical D is 63.68673331, etc..
i'm still thinking that blexting was right.. the question is supposed to have a 420.. Nobody in their right mind would assign a problem with decimals.. well unless ur dealin with physics
ok maybe i went about this the wrong way. i am look for an answer for -2x squared+76x+ 430. supposed to factor by grouping i think. trying to figure it out might have messed u
oops mean up*
I think this way it makes sense.. and if u can't factor use quadratics. it's much easier
-2x^2 + 76x + 430 = 0 by the way is it + 430 or - 430?
D = 76^2 - 4 * (-2) * 430 = 5776 + 3440 = 9216
x1 = (-76-sqrt(9216))/(2*(-2)) = (-76 - 96)/-4 = 43
x2 = (-76+sqrt(9216))/(2*(-2)) = (-76 + 96)/-4 = 20/-4 = -5
So to factor ur equation you would have: (x-43)(x+5)=0
Please click on become a fan if I helped, I really want to get to the next level!! Thanks =)
First of all if -2x^2 + 76x + 430 = 0 is the equation Then the first thing you do is to factor out the -2 (common factor) -2(x^2 - 38x - 215) = 0 Then you would be looking for factors of 215 that subtract to get 38 Which would be 43 and 5 So it would factor into -2(x - 43)(x + 5) = 0